Kontrol Pemuda Terhadap Tata Kelola Migas Dan Implikasinya Pada Ketahanan Wilayah Di Kawasan Migas Blok Cepu Kabupaten Bojonegoro - Danang Wahyuhono; Suryo Purwono; Dyah Mutiarin (Universitas Gadjah Mada, 2019)
ABSTRACTThis study aimed to analyzed form and capabilities of youth control, as well as to assessed their implications for regional resilience. Regional resilience was analyzed through the aspect of environmental, economic, social and security resilience, in which they were directly related to the oil and gas project activities in Cepu Block, namely Banyuurip area, Jambaran Tiung Biru area, and Pipe Line area. This study used qualitative methods, as it seeked to revealed the complex and deep social reality in the Cepu Block area. Using theory of access from Ribbot and Peluso (2003) which emphasized the ability of youth in controlling the flow of benefits and the impact of a resource. Control was defined as the ability to organized and directed relational actions. The flow of benefits and impacts were controlled in the form of employment benefits and Corporate Social Responsibility (CSR) programs, as well as environmental impacts. Youth had bundle of power to strengthened their control in the form of identity and social relations. This study revealed the diverse realities associated with youth control capabilities, and their implications for regional resilience. The most significant implications were environmental resilience, while economic, social, and security resilience were still vulnerable.ABSTRAKPenelitian ini bertujuan mengkaji bentuk dan kemampuan kontrol pemuda, serta implikasinya terhadap ketahanan wilayah. Ketahanan wilayah dikaji dalam gatra ketahanan lingkungan, ekonomi, sosial, dan keamanan. Penelitian ini menggunakan metode kualitatif, karena berupaya mengungkap realitas sosial yang kompleks dan mendalam di kawasan Blok Cepu. Kontrol pemuda dianalisis menggunakan teori akses dari Ribbot dan Peluso (2003) yang menekankan kemampuan pemuda dalam mengontrol aliran manfaat dan dampak dari suatu sumber daya.Kontrol didefinisikan sebagai kemampuan mengatur dan mengarahkan tindakan relasional. Aliran manfaat dan dampak yang dikontrol berupa manfaat pekerjaan dan program CSR, serta dampak lingkungan. Pemuda menggunakan ikatan kekuatan (bundle of power) untuk memperkuat kontrolnya, terutama berupa identitas dan relasi sosial. Penelitian ini mengungkap realitas yang beragam terkait kemampuan kontrol pemuda, dan implikasinya padaketahanan wilayah. Implikasi yang paling signifikan terdapat pada ketahanan lingkungan, sedangkan ketahanan ekonomi, sosial, dan keamanan masih bersifat rentan.